2022
DOI: 10.3389/fpsyt.2022.846286
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of emotion regulation in parent-mediated interventions for autism spectrum disorder

Abstract: Autistic individuals are at elevated risk for difficulties with emotion regulation (ER) that emerge early in life and are associated with a range of internalizing and externalizing disorders. Existing interventions that support ER have focused on school-age autistic children and adolescents as well as adults. Proactive approaches to improving ER in early childhood are thus needed, as is understanding the approaches by which ER skills can be feasibly supported in this young population. This review summarizes ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 83 publications
1
7
0
Order By: Relevance
“…However, many clinicians shared that the connections between core social communication strategies and emotion regulation are not explicitly discussed within intervention materials. The finding that regulation is implied in Project ImPACT, but not explicitly stated, is consistent with a recent review indicating that almost no studies of caregiver-mediated interventions for young children with autism, including NDBIs, have measured emotion regulation as an outcome (Hendrix et al, 2022). Results suggest that these connections could be made more explicit and also measured within NDBI research.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, many clinicians shared that the connections between core social communication strategies and emotion regulation are not explicitly discussed within intervention materials. The finding that regulation is implied in Project ImPACT, but not explicitly stated, is consistent with a recent review indicating that almost no studies of caregiver-mediated interventions for young children with autism, including NDBIs, have measured emotion regulation as an outcome (Hendrix et al, 2022). Results suggest that these connections could be made more explicit and also measured within NDBI research.…”
Section: Discussionsupporting
confidence: 85%
“…Despite the prevalence of disruptive behaviors among autistic children, most caregiver-mediated NDBIs do not include manualized approaches or guidelines to manage disruptive behavior (Bruinsma et al, 2020;Schreibman et al, 2015), and only a small number of studies have examined changes in disruptive behaviors or emotion regulation following participation in a caregiver-mediated NDBI (Hendrix et al, 2022). For example, Gulsrud et al (2010) demonstrated significant reductions in child negative affect and increases in maternal emotional scaffolding throughout the course of a caregiver-mediated NDBI.…”
Section: Introductionmentioning
confidence: 99%
“…In parent-mediated interventions, parents are taught a combination of techniques to promote the child's social engagement, language, imitation, and play skills. Parents are also trained to become more responsive to the children's communication style and needs, with an effect also in emotional regulation [52].…”
Section: Parent-mediated Interventionsmentioning
confidence: 99%
“…However, quantitative measures for these outcomes that are based on non-Autistic populations may not adequately capture unique Autistic perspectives and experiences (Pellicano & den Houting, 2022). Therefore, as well as a need for the development and subsequent use of outcome measures that can objectively measure these constructs with Autistic populations (Hendrix et al, 2022;Trembath et al, 2022), understanding participant perspectives may provide an important insight into the subjective outcomes of Autism support programmes (Jurek et al, 2022;Wainer et al, 2017). In this research therefore, it was a strength that parents reflected on the perceived benefits of the programme on their child's and family's outcomes.…”
Section: Quality Of Lifementioning
confidence: 99%
“…A few parents also described how their child improved their emotional regulation skills, tolerance for transitions, "rigidity" (i.e., insistence on sameness), and/or reduced their self-injurious behaviours. Challenges with emotional regulation often appear early for Autistic children and are linked to social and behavioural functioning and the development of internalising and externalising disorders during late childhood, adolescence, and adulthood (Hendrix et al, 2022). It is also possible that internal factors such as heightened anxiety can result in externalised behaviours such as insistence on sameness or challenges with transitions, as well as expressions of distress such as aggression and selfinjurious behaviours (Gotham et al, 2013).…”
Section: Increased Participationmentioning
confidence: 99%